After the Storm : Recovery and Resilience in the Caribbean - Kim, Jim Yong (Washington, DC: World Bank, 2019)
At this high-level roundtable, Jim Yong Kim, President of the World Bank Group, suggested three actions at the outset. First, in the wake of disasters like Irma and Maria we should channel resources quickly, flexibly, efficiently, and ensure that they reach those most adversely affected. Second, we need to make sure that we use all existing instruments and knowledge to help build resilience. Third, we need to think creatively and come up with innovative solutions to compounded challenges of the Caribbean: high vulnerability, low growth, and high debt. This could include designing debt for resilience initiatives, mobilizing innovative risk financing tools to better manage fiscal risks related to disorders, and mobilizing private sector participation in working out solutions.